Effects of rosuvastatin on metabolic profile: Versatility of dose-dependent effect - Hayder M Al-Kuraishy; Ali I Al-Gareeb (Wolters Kluwer Medknow Publications, 2019)
Obesity refers to an excess of body fat content causing metabolic and inflammatory disorders. Therefore, the aim of the present study was to investigate dose-dependent effect of rosuvastatin on the metabolic profile of diet-induced obesity in mice model study. A total number of 40 male Albino Swiss mice were used which divided into Group I: Control group, fed normal diet for 8 weeks (n = 10); Group II: High-fat diet (HFD) group, fed on HFD for 8 weeks (n = 10); Group III: HFD + 20 mg/kg rosuvastatin for 8 weeks (n = 10); and Group IV: HFD +40 mg/kg rosuvastatin for 8 weeks (n = 10). Anthropometric and biochemical parameters were estimated, including fasting blood glucose, lipid profile, fasting insulin, and glucose tolerance test (GTT). Mice on HFD fed showed a significant increase in the insulin resistance, body weight, deterioration of lipid profile and significant reduction in the β-cell function, and insulin sensitivity compared to the control P < 0.05. GTT and blood glucose level were significantly high in HFD fed group compared to the control group P < 0.05. Rosuvastatin in a dose of 40 mg/kg illustrated better effect than 20 mg/kg on the glucometabolic profile P < 0.05. Rosuvastatin may has a potential effect on reduction of glucometabolic changes induced by HFD with significant amelioration of pancreatic β-cell function in dose-dependent manner.